An incidental finding of duodenal GIST in a patient with penetrating abdominal trauma: A case report. (August 2021) - Pyuza, Jeremia J.; Shao, Elichilia R.; Bosco, Kenan; Lodhia, Jay; Mremi, Alex
Abstract: Introduction and importance: Duodenal Gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors of the digestive tract. The tumors are derived from interstitial cells of Cajal and usually they present as gastrointestinal bleeding or non-specific abdominal pain, but they can also be asymptomatic even when they have reached considerable size. Case presentation: We report a case of a 40-year-old male presented to our emergency department after sustaining a stab wound on the abdomen. Abdominal imaging tests weren't done; instead an emergency laparotomy was undertaken upfront in an attempt to catch up with a "golden hour". Intra-operatively, an incidental solid mass measuring 4 × 5 cm was noted on the third/fourth portion of the interior duodenal flexure. Histopathologically, the lesion demonstrated spindled shaped cells which were immunopositive for positive CD117. The patient fared well postoperatively and during subsequent follow up visits. Clinical discussion: High-risk GISTs have malignant potential. In some cases, GIST is diagnosed as incidentally finding, mostly during surgical procedure, upper endoscopy or radiological studies related to GI tract. Surgical resection is recommended curative option and its extension depends on different factors. Tyrosine kinase inhibitors are of the utmost importance in high-risk and metastatic disease. Conclusion: Even considerably large duodenal GISTs can be asymptomatic, thus incidentally found during an abdomino-pelvic imaging tests. Histopathological evaluation of the operative specimen plays a key role in assessing the need of adjuvant therapy, with a significant impact on the patients' survival. Highlights: Rare mesenchymal tumors of the digestive tract Usually asymptomatic High-risk tumors have malignant potential. Surgery is recommended curative option. Tyrosine kinase inhibitor is useful in high-risk and metastatic case.